Dermatitis in community pharmacies: a survey on italian pharmacists' management and implications on corticophobia - Corrado Giua; Nicolina P. Floris; Michele Schlich; Enrico Keber; Carlo Gelmetti (Pensoft Publishers, 2021)
Community pharmacists represent an important resource for the promotion of a safer and more effective self-management of common skin diseases, as well as the provision of educational support on therapies prescribed by clinicians, ultimately improving patients' adherence. In this study, a semi-structured survey was administered to 154 Italian community pharmacists, in order to acquire information on their counseling activity on dermatological disorders. Collected data provide an overview on the frequency and methodology of counseling offered in Italian community pharmacies, identifying knowledge gaps and misbeliefs. In particular, an overall negative opinion on topical corticosteroid therapy emerged among pharmacists, unveiling a phenomenon previously described as corticophobia. Starting from this observation, we discuss the risks for patients' adherence, associated with corticophobia among pharmacists. Lastly, we briefly report on the main tools desired by pharmacists to improve their education on dermatology, envisioning their implementation with the aim of a more effective counseling.